Profile and management of the firework-injured hand - T. Pilling; P. Govender (South African Family Practice)
Background: Numerous studies internationally highlight the devastating effects of firework-related injuries and the costs involved in treating these injuries, in addition to the calls to alter legislation to prevent these injuries from occurring. There has, however, been a paucity of research studies in the South African context that describes the complexity of the injuries sustained. The aim of this study was thus to profile the firework-injured hand and to review the management from a surgical and rehabilitation perspective.